ASSESSMENT OF THE BIOCHEMICAL CORRECTION MECHANISMS OF THE UZBEK FLORA PLANT PLANTAGO LANCEOLATA L. UNDER EXPERIMENTAL DIABETES CONDITIONS (Educator Insights: Journal of Teaching Theory and Practice, 2025)
In a laboratory study, the effect of the sum of polyphenols isolated from the plant P. lanceolata on the peroxidation process in rats with experimental alloxan-induced diabetes was studied. According to the results of the study, when the sum of polyphenols isolated from the plant P. lanceolata L., a member of the Plantaginaceae family, was administered at doses of 50 mg/kg and 100 mg/kg, the amount of lipid peroxidation products decreased compared to the control group, and the activity of antioxidant enzymes was higher than in the control group.